2015
DOI: 10.1007/s10661-015-4754-5
|View full text |Cite
|
Sign up to set email alerts
|

Do diethyl phthalate (DEP) and di-2-ethylhexyl phthalate (DEHP) influence the metabolic syndrome parameters? Pilot study

Abstract: The study objective was to determine if the healthy participants were exposed to diethyl phthalate (DEP) and di (2-ethylhexyl) phthalate (DEHP) and if this exposure could be linked to the development of metabolic syndrome. The study included 103 healthy volunteers of similar age with normal BMI values, waist circumference, total cholesterol, HDL, LDL, and triglycerides. DEP and DEHP were measured in the morning urine samples to detect monoethyl phthalate (MEP) and mono-2-ethylhexyl phthalate (MEHP). Two phthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A total of 5059 articles were identified; 108 abstracts were selected for full assessment; and 73 studies met our inclusion criteria (figure 1). Thirty studies were conducted in the USA, 17 in Europe, [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] 22 in Asia, 2 in Latin America, 86 87 1 in Africa 88 and 1 in Canada. 89 In 72 studies, the anthropometric measures of obesity were assessed by trained health professionals, and in one study, weight and height were self-reported.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5059 articles were identified; 108 abstracts were selected for full assessment; and 73 studies met our inclusion criteria (figure 1). Thirty studies were conducted in the USA, 17 in Europe, [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] 22 in Asia, 2 in Latin America, 86 87 1 in Africa 88 and 1 in Canada. 89 In 72 studies, the anthropometric measures of obesity were assessed by trained health professionals, and in one study, weight and height were self-reported.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we investigated the process of androgen-to-estrogen conversion in adipose tissue. The orientation of steroid biosynthetic pathways in adipose tissue depends on the relative expression or activity of steroid-derived enzymes [20]. We observed that the expression and concentration of CYP19 were upregulated in adipose tissue, which implies that more estrogen was being produced.…”
Section: Discussionmentioning
confidence: 72%
“…Classic steroidogenic tissues such as ovaries and adrenal glands synthesise steroid hormones de novo from cholesterol [20]. The process consists of the following steps.…”
Section: Discussionmentioning
confidence: 99%
“…Among EDCs are genistein, daidzein, bisphenol A (BPA), phthalates, perfluorooctan acid (PFOA), perfluorooctan sulfonates (PFOS), polychlorinated biphenyls (PCB) and polybromated biphenyls (PBB). Based on novel literature data EDCs have negative effect on human health even in minimal concentrations and are connected not only with the disruption of the endocrine function, but also with noninfectious diseases such as obesity, diabetes mellitus type 2, cardiovascular diseases, metabolic syndrome, as well as the influence on the reproductive health of men and women, influence on pregnancy development, formation of the fetus and fetal development and physiological growth and development of children and adolescents [38,39]. Pharmacist as one of the most available healthcare professionals has direct communication with the public, enjoys the public's trust, has the knowledge and opportunity to give professional information about the harmful effects of various anthropogenic pollutants especially endocrine disrupting chemicals [40].…”
Section: Pharmacist In the Health Protection Caused By Environmental mentioning
confidence: 99%